Balinese Phonological Interference in Indonesian Communication in The Panglipuran Village - Dea Putri Pascha; Mikail Randu R.; Tasya Febrianty; Nurmalita Herdiana; Endang Sholihatin (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2024)
This study aims to (1) know the Balinese language interference that affects the spoken pronunciation of Indonesian in Panglipuran village community and (2) Know the factors that cause Balinese Language Interference to Indonesian. This research uses qualitative research methods, data collection is done through direct interviews to data sources, namely the people of Panglipuran Village Bali. The results of this study show that, phonological interference is influenced by several phonological processes in the form of phoneme changes such as, changes in phoneme /e/ to phoneme /a/, changes in consonant phoneme /b/ to consonant phoneme /m/, changes in phoneme /e/ to phoneme /i/, changes in phoneme /a/ to phoneme /o/, changes in phoneme /e/ to phoneme /i/. Then there is the diphthong process as in the phoneme /au/ into the phoneme /o/, there is also the metathesis of the phoneme /o/ which moves to the phoneme /e/, the elision of the middle phoneme /a/, and the influence of the speaker's hypercorrection. Language interference can also be influenced by several factors such as, 1) speakers who are bilingual; 2) Balinese and Indonesian are cognate languages and; 3) the influence of the times and environmental factors.